2020
DOI: 10.1002/clc.23319
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of sleep apnea and nocturnal hypoxemia in patients with decompensated heart failure

Abstract: Background Nocturnal hypoxemia is an important factor underlying the impact of sleep apnea on heart failure. It remains unclear whether nocturnal hypoxemia has a greater prognostic value in acute decompensated heart failure (ADHF) compared with the frequency of sleep apnea. Hypothesis Nocturnal hypoxemia might be better than the frequency of sleep apnea in predicting the outcomes in ADHF. Methods Sleep studies were prospectively performed during an ADHF hospitalization from January 2015 to December 2017. Sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…According to the present study, patients with adverse events had a comparable AHI to those without an endpoint (p = 0.9). The limited role of AHI in HF is noted by many authors [10,11]. The severity of apnea, and most importantly its effect on outcomes, may be determined not only by AHI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the present study, patients with adverse events had a comparable AHI to those without an endpoint (p = 0.9). The limited role of AHI in HF is noted by many authors [10,11]. The severity of apnea, and most importantly its effect on outcomes, may be determined not only by AHI.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al, in a prospective cohort study, also demonstrated the prognostic role of nocturnal hypoxemia in patients with HF. A multivariate Cox regression analysis found that a saturation below 90% was independently associated with the outcome (hazard ratio [HR] 1.008, 95% confidence interval [CI] 1.001-1.016, p = 0.033), while no such association was found for AHI [11]. However, in the present study, the group with adverse events and the group without a combined endpoint had a comparable SpO 2ave (p = 0.4), SpO 2min (p = 0.5), ODI (p = 0.3), according to ROC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Only periods with sufficient airflow and oxygen saturation signals at the same time were regarded as an effective recording. We considered only sleep monitoring with at least 4 h of adequate recording time as described previously 19 . Based on the American Academy of Sleep Medicine, 20 apnea and hypopnea were scored as a ≥90% and ≥30% decrease in breathing amplitude, respectively, for ≥10 s. At the same time, hypopnea‐related decreases were ≥3% oxygen desaturation.…”
Section: Methodsmentioning
confidence: 99%
“…We considered only sleep monitoring with at least 4 h of adequate recording time as described previously. 19 Based on the American Academy of Sleep Medicine, 20 apnea and hypopnea were scored as a ≥90% and ≥30% decrease in breathing amplitude, respectively, for ≥10 s. At the same time, hypopnea‐related decreases were ≥3% oxygen desaturation. The apnea‐hypopnea index (AHI) was determined using apnea plus hypopnea events per hour of sleep.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 In particular, SAS has been shown to be associated with a worse prognosis of patients with heart failure, with an increased incidence of both ventricular arrhythmias and recurrent hospitalizations for decompensated heart failure. 3,4 On the other hand, currently available devices, as implantable cardioverter defibrillators (ICDs) and biventricular pacemakers, have been shown to reduce mortality by decreasing sudden arrhythmic death 5 and improving systolic function in patients with evidence of severe left ventricular dysfunction. 6,7 These devices are now also able to monitor indexes of cardiovascular and respiratory function over long-term periods.…”
Section: Introductionmentioning
confidence: 99%